The Intellectual in Twentieth-Century Southern Literature - Powell, Tara, 1976- (Book collections on Project MUSE., 2012)
Never in its long history has the South provided an entirely comfortable home for the intellectual. In the thought-provoking The Intellectual in Twentieth-Century Southern Literature Tara Powell considers the evolving ways that major post-World War II southern writers have portrayed intellectualsfrom Flannery OConnors ironic view of interleckchuls to Gail Godwins southerners striving to feel at home in the academic world.